Desarrollo de una vacuna profilactica de segunda generacion contra el papilomavirus humano - Alonso, Leonardo Gabriel (2011)
Human papillomaviruses (HPV) are the etiologic agent for cervical cancer (CC), the second cause of cancer death in women worldwide. It is estimated that half a million new cases are diagnosed each year, mostly in developing countries due to the lack of massive programs for early detection of the virus. Recently, two prophylactic vaccines against the main oncogenic HPV types 16 and 18 (responsible for 80% of CC) have been introduced into market. Both of these vaccines, obtained as recombinants, have been shown to be safe and effective; however, their high cost works against its immediate impact in the incidence of HPV infection in developing and low-income countries. There is a need to have in hand second generation, low cost vaccines of massive use that will decrease CC cases in a large extent. With this in mind, we have developed a recombinant expression platform that allows us to obtain virus-like particles (VLPs) to formulate both effective and accessible vaccines against HPV infection.